Preferred field of study and academic performance - Francesco Berlingieri; André Diegmann; Maresa Sprietsma (Halle Institute for Economic Research (IWH), 2022)
This paper investigates the impact of studying the first-choice university subject on dropout and switching field of study for a cohort of students in Germany. Using detailed survey data, and employing an instrumental variable strategy based on variation in the local field of study availability, we provide evidence that students who are not enrolled in their preferred field of study are more likely to change their field, delay graduation and drop out of university. The estimated impact on dropout is particularly strong among students of low socio-economic status and is driven by lower academic performance and motivation.
urn:nbn:de:gbv:3:2-881552
Keywords: I21; I23; J24; 330; academic performance; field of study; preferences; university dropout